2014
DOI: 10.1021/am500081e
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Matrix Membranes with Strengthened MOFs/Polymer Interfacial Interaction and Improved Membrane Performance

Abstract: MOFs-based mixed matrix membranes (MMMs) have attracted extensive attention in recent years due to their potential high separation performance, the low cost, and good mechanical properties. However, it is still very challenging to achieve defect-free interface between micrometer-sized MOFs and a polymer matrix. In this study, [Cd2L(H2O)]2·5H2O (Cd-6F) synthesized using 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) as an organic ligand was introduced into the 6FDA-ODA polyimide matrix to achieve no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
123
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 46 publications
2
123
0
Order By: Relevance
“…Interestingly, additive interactions with chain terminal groups appear to reinforce nanocomposite films, whereas strong side group interactions seem to compromise mechanical performance; highlighting the influence of additive interactions on polymer conformation. 20,23,50,67 …”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, additive interactions with chain terminal groups appear to reinforce nanocomposite films, whereas strong side group interactions seem to compromise mechanical performance; highlighting the influence of additive interactions on polymer conformation. 20,23,50,67 …”
Section: Figmentioning
confidence: 99%
“…21,22 High additive loading generally causes severe embrittlement, though a few recent studies have reported stable MMM films through targeted polymer-additive interactions. 12,[23][24][25][26] Similarly, adsorption of polymer chains in super-porous additives have been used to stop age-related permselectivity loss in glassy MMM. 12,[27][28][29] To date, there is no complete model describing the complex polymer-additive interactions responsible for MMM properties and little is known about how additive incorporation affects the mechanical resilience of polymer nanocomposites with aging.…”
Section: Introductionmentioning
confidence: 99%
“…These microporous materials have been proposed for H2, CH4 and CO2 capture/adsorption and often exhibit high uptake capacities 26 . Other materials, specifically addressed to gas capture and storage are based on mixed matrix membranes, combining both zeolite and polymers 27 , or MOFs and polymers 28 . Hyper-Crosslinked Polymers (HCPs) are a class of low cost porous organic networks easily prepared by Friedel-Crafts reaction.…”
Section: Introductionmentioning
confidence: 99%
“…An interfacial void-free MMM with high gas separation performance has been achieved [31]. The last but also important strategy is to eliminate the formation of non-selective interfacial voids via in-situ polymerisation [32][33][34]. Also, introducing a cross-linkable polymer (e.g.…”
Section: Introductionmentioning
confidence: 99%